DAMPAK VARIABILITAS IKLIM TERHADAP PRODUKSI PANGAN DI SUMATERA - Sinta Berliana Sipayung (Jurnal Sains Dirgantara, 2005)
Food security will become unstable if extreme climate occurred frequently, such as dry and rainy season more than normal condition. This condition will have positive and negative effects, especially on agriculture sector. In this study, effect of climate variability on agriculture production over Sumatera Island for ten years (1991-2000) observation will be discussed. The result show that part of Sumatera Island has more surplus than deficit, so it has more planting season in one year. We suspect that El-Nino event has more effect than La-Nina event in decending crop agriculture productivity at Sumatera Island who has Monsoon raifall pattern.